A Critical Evaluation of Power Quality Features using Dual APF under Grid Interfaced DG Scheme - Yadiki Rajendra Babu; C Srinivas Rao (Institute of Advanced Engineering and Science, 2017)
This paper presents the concept of power quality enhancement reducing the harmonic distortion with power distribution system consisting of balanced and unbalanced non-linear type of loads. This paper presents power quality enhancement using dual active power filters (APF’s) under grid connected distributed generation scheme. Acive power filters effectively generate compensating signals for harmonic abolition and this paper presents APF for compensating currents to be induced in to distribution grid for harmonic elimination under balanced and unbalanced non-linear load conditions. Distributed generation (DG) feeds the grid and the scheme of grid interfaced DG was explained. APF is controlled using instantaneous P-Q theory and DG inverter is controlled using simple control strategy. Proposed system was developed and the results are obtained using MATLAB/SIMULINK software.